Developing Students’ Vocabulary in English Speaking Ability By Using Talk-Show Video as Directed Practice Media - Ichwan Purwata (Universitas Hamzanwadi, 2018)
This research is aimed to: (1) identity whether and to what extent talk show video as a directed practice media to improve students’ vocabulary in speaking ability and (2) describe classroom climate when talk show video as a directed practice media was applied in the speaking class. The method used in this research was classroom action research. The research findings showed that talk show video in teaching and learning English could improve the students’ vocabulary in speaking ability and the classroom climate. Video could stimulate and motivate students’ interesting in improving their vocabulary in speaking class. As a result, talk show video is suitable for supporting and developing students’ speaking ability. It has an important role in teaching and learning process.